Aktualisasi Pendidikan Fikih Lingkungan (Fiqh Al-Bi’ah) pada Masyarakat Kawasan Hutan Desa Genggelang Kecamatan Gangga Kab. Lombok Utara - Sujono Indrajati; Emawati Emawati; Muh. Azkar (MANAZHIM, 2023)
Nature or the environment cannot be separated from the social life of society. The actualization of environmental fiqh education (fiqh al-bi'ah) in society is considered capable of minimizing problems in forest area environmental cases. This research aims to find out about understanding public to draft education jurisprudence environment (Fiqh Al- bi'ah) in society area forest Village Gang, education jurisprudence environment conducted in schools/madrasah and analyze actualization education Fiqh Al- bi'ah in society area forest Village Gang. This study uses descriptive qualitative methods with observation, interviews, and documentation techniques. The community already has awareness and is able to properly manage the forest area environment in accordance with Islamic teachings and applicable regulations. This study concludes, the actualization of environmental law education (fiqh al-bi'ah) in the forest area community of Genggelang Village includes: First, Understanding of the Forest Area Community Village Gangbang To Draft Jurisprudence Environment (Fiqh Al- Bi'ah ), As for what is obtained , researchers find a number of perspective about understanding public to draft education jurisprudence environment ie Perspective public intellectual or educated is society that has base education from medium on until college high . Then own more knowledge in field general nor religion. Second, Fiqh Education Environment in Schools /Madrasahs, and Third, Actualization of Jurisprudence Education Environment (Fiqh Al- Bi'ah) in Forest Area Communities Village Gang.